Grenada. Annual report 2018 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
The Grenada Delegation of the Inter-American Institute for Cooperation on Agriculture (IICA) wishes to compliment our stakeholders for their contributions and support to the achievements in this Annual Report for 2018. The achievements of the technical cooperation activities undertaken this year are to inform stakeholders and partners of our shared accomplishments. We have consulted with various stakeholders’ groups during our planning process and are now accounting through the report that provides the opportunity for stakeholders to evaluate what was achieved.